5237 sayılı Türk Ceza Kanunu’na göre rüşvet suçu - Aldemir, Zeynep (My University, 2011)
Bu tezin konusu 5237 Sayılı Türk Ceza Kanunu’nda düzenlenen rüşvet suçudur. Tez, giriş ve sonuç bölümü dışında üç bölümden oluşmuştur. Giriş bölümünde, konunun takdimi ve çalışma metoduna yer verilmiştir. Birinci bölümde, önce rüşvet suçunun kamu idaresinin güvenilirliğine ve işleyişine karşı suçlardan olması sebebiyle, bu kategorideki suçların genel özelliklerine değinilmiş; sonrasında rüşvet suçunun faili olması sebebiyle kamu görevlisi kavramı incelenmiştir. Daha sonra rüşvet kavramı incelenmiştir. Rüşvet suçunu daha iyi anlayabilmek açısından rüşvet suçunun tarihi gelişimine değinilmiştir. İkinci bölümde ise, önce rüşvet suçunun yapısı, rüşvet anlaşması ve rüşvet suçunun koruduğu hukuki değer, sonra rüşvet suçunun unsurları incelenmiştir. En sonunda da, suçun özel görünüş şekilleri incelenmiştir. Üçüncü bölümde, muhakeme usulleri, zamanaşımı, etkin pişmanlık halleri ve rüşvet suçunun yaptırımı konusu ve rüşvet suçunun diğer benzer suçlardan ayrımı konusu işlenmiştir. Sonuç bölümünde ise, çalışmamızın değer kazanması açısından kendi çıkarımlarımızla birlikte uygulayıcılara daha yararlı olabileceğini düşündüğümüz bilgilere yer verilmiştir. Çalışmamın herkese faydalı olması temennisiyle.

The subject matter of this thesis is the crime of bribery which is regulated under Law No. 5237 Turkish Penal Code. The thesis is consisting of three chapters in addition to the introduction and consequence parts. In the introduction part, it has been aimed to present the subject matter and working method. In the first chapter, the category of crimes committed against the reliance of public administration and the concept of public official as offender of crime of bribery have been analyzed due to the fact that the crime of bribery is categorized as a crime committed against the reliance of public administration. Afterwards, the definition of bribe has been specialized. In order to better understand bribery, it has been touched upon the historical development of this crime. In the second chapter, the structure of the crime of bribery, the conspiracy to commit bribery and the elements of the crime of bribery has been aimed to be presented. At the end of this chapter, special aspect types of crime have been analyzed. In the third chapter, proceedings, period of prescription, effective withdrawal, the sanctions for bribery and the differences of crime of bribery than the similar ones have been examined. In the consequence part, for the sake of making our dissertation more valuable to the readers, there has been given our conclusion and the information which might be beneficial to the practitioners. I wish that everyone can benefit from this intellectual work.
Keywords: Ceza Hukuku; Hukuk; Rüşvet_Hukuk